HUBUNGAN PEMBERIAN ASI DENGAN KENAIKAN BERAT BADAN PADA BAYI BERAT BADAN LAHIR RENDAH (BBLR) DI RUANG NICU RSUD DR. MOHAMAD SALEH KOTA PROBOLINGGO: The Correlations Between Breastfeeding and Low Birth Weight (LBW) in the NICU RSUD Dr. Mohamad Saleh, City of Probolinggo - Juriyah; Muthmainnah Zakiyyah; Homsiatur Rohmatin (Forind Press, 2023)
Low Birth Weight Babies is a baby born weighing less than 2,500 grams who was weighed from birth to the first 24 hours after birthThe research design in research was correlational analytic research. The population in this study were all LBW babies who were breastfed in February as many as 30 people in February 2023 as many as 30 people. The number of samples is 30 people with the total sampling technique. Collecting data using a questionnaire then the data is processed using SPSS using Chi-squareThe results of the analysis showed that most of the respondents were breastfed, namely 20 people (66.7%), for the baby's weight gain while being breastfed, there were 20 people (66.7%) while the results of the Chi-Square test between AS givers with an increase in baby's weight obtained a p-value of 0.000 (p-value) (smaller than 0.05) so there is a significant correlation between the variable breastfeeding and infant weight gain.One of the benefits of breastfeeding for babies can be seen from the nutritional aspect of babies. Breast milk contains many nutrients, including albumin, fat, carbohydrates, vitamins, minerals, growth factors, hormones, enzymes, immune substances, and white blood cells, in the right and balanced portions. The child's weight gain is greatly influenced when the child gets adequate food intake, the energy-rich food needed by the child for the purposes of basal metabolism, growth and activity.